Integration of Wifi and Mobile Communications in Fire Early Warning Data Sending in Home Based on The Internet of Things - Fadli Tamrin; Asrul Asrul; arman arman (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
House fires are one of the disasters that are often encountered in the community, especially when the area is a dry geographical area. Not to mention the catastrophic house fires that took the most lives and losses for homeowners. The purpose of this research is how to build a disaster early warning system by utilizing the integration of wifi and cellular communications. In this study using blackbox testing and hardware testing methods as well as several tools such as Arduino Mega2560, ESP32, DHT-22, MQ-2, LDR Array, SIM900, Pump Mini DC and Fan Mini DC. After the results of the system design, where the system works with online and offline conditions and as well as each sensor works according to the input conditions of fire, gas and smoke. In addition, this device can help the community in avoiding fires for both home and industrial fires. This device will make everyone feel safe because it can detect a fire.